The Effect of Spiritual Leadership on Employee Effectiveness: An Intrinsic Motivation Perspective - Wang, Minghui; Guo, Tengfei; Ni, Yakun; Shang, Sudong; Tang, Zheng (Frontiers in Psychology, 2019)
Drawing on spiritual leadership theory and intrinsic motivation theory, we proposed a homologous multilevel model to explore the effectiveness of spiritual leadership on employees’ task performance, knowledge sharing behaviors and innovation behaviors at the individual level. With questionnaires rated by 306 pairs of employees and their supervisors in 26 teams from the energy industry in mainland China, we conduct multilevel analysis to examine our hypotheses. The results show that spiritual leadership was positively related to employee task performance, knowledge sharing behaviors and innovation behavior, when we controlled for possible confounding effects of moral leadership and benevolent leadership, and ruled out alternative explanation of ethical leadership. The theoretical and practical implications are discussed.